Evaluation of Antibacterial Enrofloxacin in Eggs by Matrix Solid Phase Dispersion-Flow Injection Chemiluminescence - Xiaocui Duan; Pingping Zhang; Jing Feng; Ning Jiao (Journal of Chemistry)
The study based on the chemiluminescence (CL) reaction of potassium ferricyanide and luminol in sodium hydroxide medium, enrofloxacin (ENRO) could dramatically enhance CL intensities and incorporated with matrix solid-phase dispersion (MSPD) technique (Florisil used as dispersant, dichloromethane eluted the target compounds). A simple flow injection chemiluminescence (FL-CL) method with MSPD technique for determination of ENRO in eggs was described. Under optimal conditions, the CL intensities were linearly related to ENRO concentration ranging from 4.0×10-8 g.L−1 to 5.0×10-5 g.L−1, with a correlation coefficient of 0.9989 and detection limit of 5.0×10-9 g.L−1. The relative standard deviation was 3.6% at an ENRO concentration of 2.0×10-6 g.L−1. Our testing technique can help ensure food safety, and thus, protect public health.